Current regulatory requirements and practical approaches for stability analysis of pharmaceutical products: a comprehensive review - Sengupta, Pinaki Ranjan; Chatterjee, Bappaditya; Tekade, Rakesh (Elsevier B.V, 2018)
Different regulatory guidelines recommend establishing stability profile of pharmaceuticals at the time of drug development. The expiry date, retesting period and storage conditions of active drugs or products are established through stability analysis. Several regulatory guidelines exist for stability testing of pharmaceuticals. Mostly, ICH stability guidelines are followed in practice. This guideline recommends to validate stability indicating method using forced degradation samples that contains all possible degradation impurities. ICH guidelines provide general recommendations for inclusion of stability indicating parameters in a stability testing protocol. However, those guidelines do not provide specific requirements and experimental methodology to be followed for stability studies. Due to this gap, often confusion arises in the scientific community in designing stability testing protocol. Therefore, significant variations are observed in reported literature in selection of stability indicating parameters. Procedural dissimilarity amongst reported stability studies is also evident. This review discusses the regulatory guidelines and procedures to follow in performing stability testing of pharmaceuticals. Scope of this review also includes recommendations on practical approaches for designing stability testing protocol to fulfill current regulatory requirements for drug substances and their formulations.